2023
DOI: 10.1093/evolinnean/kzad003
|View full text |Cite
|
Sign up to set email alerts
|

Perfect storms shape biodiversity in time and space

David Jablonski,
Stewart M Edie

Abstract: Many of the most dramatic patterns in biological diversity are created by “Perfect Storms” —rare combinations of mutually reinforcing factors that push origination, extinction, or diversity accommodation to extremes. These patterns include the strongest diversification events (e.g. the Cambrian Explosion of animal body plans), the proliferation of hyperdiverse clades (e.g. insects, angiosperms), the richest biodiversity hotspots (e.g. the New World Tropical Montane regions and the ocean's greatest diversity pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 134 publications
0
1
0
Order By: Relevance
“…Diversity-dependence on macroevolutionary scales remains a difficult but engaging problem, and the stakes are high for determining proximate and ultimate causes given the environmental and climatic turmoil now challenging today's biodiversity [ 81 ]. Fossil data have long shown that diversification dynamics in response to episodes of major environmental and climatic change can yield accelerated rebounds in biodiversity following catastrophic losses during mass extinctions.…”
Section: Resultsmentioning
confidence: 99%
“…Diversity-dependence on macroevolutionary scales remains a difficult but engaging problem, and the stakes are high for determining proximate and ultimate causes given the environmental and climatic turmoil now challenging today's biodiversity [ 81 ]. Fossil data have long shown that diversification dynamics in response to episodes of major environmental and climatic change can yield accelerated rebounds in biodiversity following catastrophic losses during mass extinctions.…”
Section: Resultsmentioning
confidence: 99%